Modeling of the dynamic mechanical properties of the coagent reinforced row hydrogenated poly(butadiene-co-acrylonitrile) (HNBR) and the morphology of coagent nanodispersions in HNBR matrix - Likozar, B.; Krajnc, M. (Polimery, 2022)
Coagents are typically used for crosslinking of synthetic elastomers and are ordinarily used to achieve excellent properties of the crosslinked products. Dynamic mechanical properties of two different types of reinforcing coagents and not cured hydrogenated poly(butadiene-co-acrylonitrile) compounds were investigated and modeled. The function of zinc dimethacrylate (ZDMA) inverted with loading in the mixtures from filler-like (up to 13phr) into plasticizer-like behavior (over 13phr). Nevertheless, trimethylolpropane trimethacrylate (TMPTMA) as a reinforcing substrate exhibited a reinforcing effect during the glass transition and plateau region throughout the investigated loading range. Morphology evolved during processing changed in parallel with the results obtained from dynamical mechanical analysis (DMA) of the blends. Both in the case of ZDMA and TMPTMA micro- and nano-phases evolved during mixing. The volume fractions of the particles under 100nm in ZDMA and TMPTMA blends ranged from 16 to 89%. Dynamic mechanical properties were modeled using a continuous relaxation distribution function, Williams-Landel-Ferry (WLF) equation and the modified Guth-Gold equation. The measured dynamic mechanical properties of not cured compounded elastomers containing coagents/fillers are of a great importance in connection with processing operations, which could be designed with aid of the proposed model.